Pengaruh Equality To Total Assets Ratio, Non Performing Ratio dan F9inancing To Deposit Ratio Terhadap Kinerja Keuangan Koperasi BMT Nurul Jannah Gresik Tahun 2012-2014 - Anastasia, Febby Karina; Septiarini, Dina Fitrisia (Jurnal Ekonomi Syariah Teori dan Terapan, 2015)
This research aimed to know the influence of Equity to Total Assets Ratio, Non Performing Ratio and Financing to Deposit Ratio to Return on Assets Ratio in BMT Nurul Jannah Gresik. This research used the quantitative approach method. The analysis technique used multiple linear regression.Based on the result of t-test, Equity to Total Assets Ratio and Financing to Deposit Ratio partially did not influence significantly to Return on Assets Ratio, but Non Performing Financing influenced significantly to Return on Assets Ratio. The result of simultaneous test showed that Equity to Total Assets Ratio, Non Performing Ratio and Financing to Deposit Ratio had significant effect to Return on Assets Ratio with siginificant value 0,001. The ability of Equity to Total Assets Ratio, Non Performing Ratio and Financing to Deposit Ratio in explainingReturn on Assets Ratio of 38,3% and the remaining 61,7% was explained by other variables outside the model.